The Relationship Between Family Support and Elderly Independence Towards the Self-Concept of the Elderly in The Village Area Jatijajar City of Depok - Saka Adhijaya Pendit; Dayuningsih (Comprehensive Health Care, 2025)
Aging is a natural process in the stages of human life that will affect their health status. Various problems that arise in the elderly are functional consequences of biological, psychological, social, and spiritual changes. Changes that occur in old age can cause dependence on their closest family, be it their spouse or grandchildren.Changes in the elderly, both physically, mentally and emotionally, require family support, because family support helps with elderly problems. In order for the elderly to enjoy life in old age so that they can be happy or feel happy, support is needed from people close to them. This support aims to ensure that the elderly can continue to carry out daily activities regularly and not excessively. This study aimsAnalyzing the relationship between family support and elderly independence towards the concept of elderly self in the Jatijajar Urban Village, Depok City. This type of research isdescriptive correlation research, using a cross-sectional design.The population in this study was all elderly people who were inJatijajar sub-district area of ​​Depok city.The sample in this study was taken based on inclusion and exclusion criteria with a sample size of 78 people. The results of statistical tests using the chi square test showed a p-value = 0.000 smaller than the value of α = 0.05, which means that there is a relationship between family support and elderly independence with the self-concept of the elderly in the Jatijajar Village Area, Depok City.This research is expected to provide information to the general public and patient families that there are many factors such as family support and elderly independence that can influence the elderly's self-concept.